Models for very high speed fets - Çil, Celal Zaim. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
In recent years,the semiconductor electronic industry has entered the Very Large Scale Integration(VLSI) era, in which individual integrated circuits are characterized by increasingly complex circuitry and technology. Progress in the microelectronics area will continue to be tied to the ability to continue to put ever increasing numbers of smaller devices on a chip. In the submicron device size range, it is expected that transport will be limited by the saturation velocity. Therefore, the devices should be very fast and be fabricated with very small dimensions. A new transistor which can meet these requirements bas appeared on the scene. This transistor, called MODFET which is a device evolved from the work on GaAs-AlGaAs superlattices(thin alternating layers of different materials sharing the same crystalline lattice) shows some superior properties because of high mobilities achieved in GaAs since electrons transfer from the doped wider band gap AlGaAs to an adjacent undoped GaAs layer, a process now called modulation doping. Models to predict the characteristics of MODFET are investigated and a new analytical model is introduced.This new model,called Mobility-Dependent Model and based on the field dependent velocity approximation, seems to be the be at model for-this type of device so far.
Keywords: Very high speed integrated circuits.; Integrated circuits -- Very large scale integration.; Transistors.; Gallium arsenide semiconductors.